Effect of Work Experiance and Work Environment On Job Satisfaction - Handayani Hasan (BJRM (Bongaya Journal of Research in Management), 2021)
This study aims to determine the effect of work experience and work environment on job satisfaction. This research was conducted on employees of the Office of Industry and Trade of South Sulawesi Province. Data collection in this research uses primary data obtained from a questionnaire (questionnaire). The selection of the sample in this study used a saturated sampling technique. The results of this study indicate that; Work Experience has a positive and significant effect on Job Satisfaction. Work Environment has a positive and significant impact on Job Satisfaction. And Work Experience and Work Environment simultaneously have a positive and significant impact on Job Satisfaction at the Office of Industry and Trade of South Sulawesi Province.